Câmara de prevenção e solução consensual de conflitos na Administração Pública: uma análise da viabilidade de sua implementação no âmbito da Procuradoria do Município de Imperatriz/MA como instrumento pragmático de superação da cultura do litígio envolvendo o poder público municipal - OLIVEIRA, Allen Kardec Feitosa (2021)
The research analyzed the feasibility of implementing the chamber for the prevention and consensual solution of conflicts within the scope of the municipal public administration of Imperatriz / MA as a pragmatic response to the culture of litigation. It started from the innovations brought with resolution n. 125/2010 of the CNJ and driven by the current Civil Procedure Code (Law No. 13,105 / 2015) and the New Mediation Framework (Law No. 13,140 / 2015), which assert that it is up to the State to promote mediation and conciliation, as well as the possibility of institutionalizing self- composition, through the implementation of the prevention chambers and consensual resolution of public power conflicts. The hypothetical-deductive method was adopted, in addition to the bibliographic and documentary research techniques on the themes, pragmatism of everyday life, adequate methods of conflict resolution, multiport court and consensus in Public Administration. It looked at the reality of the Municipality of Imperatriz / MA, analyzing the amount of demands filed in 2019 in the court specialized in the achievements of the public farm in the district involving the municipality, as well as about the organizational structure of the Municipal Attorney and the feasibility of implementing the conflict prevention and resolution chamber within its scope of action. At the end, the theoretical reflections were confronted with the reality of the Brazilian justice system and the municipality of Imperatriz, from the survey of the level of congestion of the Judiciary, based on the recent reports of the CNJ, Justice in Numbers 2019 and 2020 and the study of the organization and functioning of the Federal Administration's Conciliation and Arbitration Chamber.